Persepsi Karyawan terhadap Penggunaan Teknologi Informasi pada Maju Ban Tirezone Manado - Supit, Kinanti Desenia; Tatimu, Ventje; Sambul, Sofia A. P. (Productivity, 2020)
This study aims to determine employee perceptions of the use of information technology. This research uses descriptive method with frequency distribution analysis techniques and percentages. The results of this study indicate that the employees of Maju Ban Tirezone Manado believe that the use of information technology is very useful in carrying out work, and can support in carrying out their duties. Employees' perceptions are related to the usefulness of information technology, ease of use of information technology, attitudes towards information technology, behavioral intentions to use information technology, and behavior in using information technology. There are no differences in perceptions due to differences in gender, age and education level.